Fuel sensitivity effects on dual-mode dual-fuel combustion operation for different octane numbers. (1st December 2019) - García, Antonio; Monsalve-Serrano, Javier; Villalta, David; Sari, Rafael
Highlights: Experimental results combined with chemical kinetics calculations. Three sensitivities tested for two fuels of research octane number 92.5 and 80. The sensitivity affects the combustion at low and medium load for octane number 92.5. Low effect of the sensitivity for research octane number 80 at low and medium load. Abstract: The dual-mode dual-fuel combustion is a promising combustion concept to achieve the required emissions and carbon dioxide reductions imposed by the next emissions standards. Nonetheless, since the combustion concept relies on the reactivity of two different fuels (diesel and gasoline), the fuel formulation requirements are stricter. This work investigates the effects of the low reactivity fuel sensitivity for different octane numbers at different operating conditions representative of the combustion regimes found inside the dual-mode dual-fuel engine map. For this, experimental evaluations were performed using fuels with research octane number 92.5 and 80 and different sensitivities (0, 5 and the maximum one achievable for each fuel). The combustion development was assessed by means of the heat release rate characterization. Moreover, numerical simulations in a constant volume homogeneous reactor were used to explore and understand the impact of the different fuels on the ignition delay time. The results suggest that the sensitivity increase affects the different research octane number fuels in a different way. For the fuel with research octane number 92.5, the sensitivity variation increases the experimental ignition delay, impairing the combustion process and increasing the fuel consumption. In the case of the fuel with research octane number 80, the sensitivity increase does not affect the combustion development. This was justified by the numerical investigation, which points to a wider temperature range where the sensitivity does not affect the final ignition delay for research octane number 80. Moreover, generally, the ignition delay times for research octane number 80 considering the experimental gasoline fraction used are half than those of research octane number 92.5. At full load conditions, the trend is inverted, where the experimental ignition delay for research octane number 80 is affected by the sensitivity whilst research octane number 92.5 presents only modifications after the combustion start.